1983
DOI: 10.1002/cne.902160203
|View full text |Cite
|
Sign up to set email alerts
|

Projections of nucleus caudalis and spinal cord to rrainstem and diencephalon in the hedgehog (Erinaceus europaeus and Paraechinus aethiopicus): A degeneration study

Abstract: In the light of hypotheses related to the evolution of pain-carrying systems in mammals, terminal projection fields in brainstem and diencephalon of efferents of nucleus caudalis (NC) of the spinal trigeminal complex and spinal cord were determined in hedgehog by using Nauta-Gygax and Fink-Heimer silver techniques for degeneration. Unilateral NC lesions resulted in medullary degeneration in the ventral portion of NC contralaterally and bilaterally in cuneate nucleus (CU) and reticular formation. Pontine degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…This anatomical difference reinforces the physiological and pharmacological differences observed between sVi and sVc (Bereiter, 1997; Hirata et al, 2000, 2004). In general, the distribution of labeled neurons demonstrated in this study is reminiscent of a distribution pattern shared by other mammalian species, including rats (Falls, 1984a; Jacquin et al, 1990b; Voisin et al, 2002), cats (Carpenter and Hanna, 1961; Stewart and King, 1963; Hockfield and Gobel, 1982; Ikeda et al, 1982, 1984; Panneton and Burton, 1982; Lovick and Wolstencroft, 1983; Somers and Panneton, 1985; Nasution and Shigenaga, 1987), hedgehogs (Ring and Ganchrow, 1983), sheep (Roberts and Matzke, 1971), and other non-human primates (Dunn and Matzke, 1968; Kruger, 1971; Tiwari and King, 1974; Smith, 1975; Kruger et al, 1977; Ganchrow, 1978) suggesting a common mammalian pattern.…”
Section: Discussionmentioning
confidence: 98%
“…This anatomical difference reinforces the physiological and pharmacological differences observed between sVi and sVc (Bereiter, 1997; Hirata et al, 2000, 2004). In general, the distribution of labeled neurons demonstrated in this study is reminiscent of a distribution pattern shared by other mammalian species, including rats (Falls, 1984a; Jacquin et al, 1990b; Voisin et al, 2002), cats (Carpenter and Hanna, 1961; Stewart and King, 1963; Hockfield and Gobel, 1982; Ikeda et al, 1982, 1984; Panneton and Burton, 1982; Lovick and Wolstencroft, 1983; Somers and Panneton, 1985; Nasution and Shigenaga, 1987), hedgehogs (Ring and Ganchrow, 1983), sheep (Roberts and Matzke, 1971), and other non-human primates (Dunn and Matzke, 1968; Kruger, 1971; Tiwari and King, 1974; Smith, 1975; Kruger et al, 1977; Ganchrow, 1978) suggesting a common mammalian pattern.…”
Section: Discussionmentioning
confidence: 98%
“…Gould and Ebner (1968b) investigated interlaminar connections and found that both vertical and horizontal connections are important and that horizontal projections originate at three distinct cortical depths. Earle and Matzke (1974), Schroeder and Jane (1976), Ganchrow and Ring (1979), and Ring and Ganchrow (1983); in Hemiechinus auritus by Earle and Matzke (1974) and Moore et a1. (1977); and in Paraechinus aethiopicus by Ring and Ganchrow (1983).…”
Section: Histology Histochemistrymentioning
confidence: 94%
“…Earle and Matzke (1974), Schroeder and Jane (1976), Ganchrow and Ring (1979), and Ring and Ganchrow (1983); in Hemiechinus auritus by Earle and Matzke (1974) and Moore et a1. (1977); and in Paraechinus aethiopicus by Ring and Ganchrow (1983). Schroeder et al (1970) mentioned projections from the dorsal column of the spinal cord, cerebellar nuclei, and tectum to the thalamus.…”
Section: Histology Histochemistrymentioning
confidence: 94%
See 1 more Smart Citation
“…The thalamus was studied because it plays an important role in the limbic aspects of nociception (16) and receives sensory signals from the pulp via the secondary afferents from the trigeminal brainstem complex (7,8). We conducted immunohistochemical and gene expression analysis for selected antigen-presenting cell-related molecules in the thalamus at 24 hours after pulp exposure, when the coronal pulp is inflamed and undergoing necrosis but the root pulp tissue is still vital (17).…”
mentioning
confidence: 99%